Development of Picture Storybooks with TheoAnthropoEco Centric Approach for Elementary School Students - Yuni Setia Ningsih; Mulia Mulia; Azmil Hasan Lubis (STAI Hubbulwathan Duri, 2023)
Learning media has a significant role in an effort to help abstract concepts so that students more easily understand these concepts. However, many teachers have difficulty in developing learning media. This study aims to develop learning media in the form of picture storybooks with a TheoAnthropoEco-centric approach that is feasible and practical for use by elementary school students. This study uses a research and development type that refers to the development stage of Borg Gall. The data was obtained using a product feasibility validation questionnaire and a teacher and student response questionnaire. The subjects of this research are media experts, material experts, linguists, class teachers and fourth-grade students of madrasah ibtidaiyah. The determination of research subjects is done by purposive sampling technique. Descriptive statistical techniques analyzed the data obtained in this study. The results showed that the picture book with the TheoAnthropoEco-centric approach developed in this study was feasible and practical for use by elementary school students. This is evidenced by the feasibility test results, which show the developed media is in the